A New Paranormed Sequence Space Defined by Regular Bell Matrix - Murat Karakaş; Muhammet Cihat Dağlı (Dera Natung Government College Research Journal)
This paper aims to construct a new paranormed sequence space by the aid of a regular matrix of Bell numbers. As well, its special duals such as α−,β−,γ−  duals are presented and Schauder basis is determined. Moreover, certain matrix classes for this space are characterized.